Strategies for creating inclusive learning for learners experiencing barriers to learning - Nzuza, Zakhele Dennis (REID (Research and Evaluation in Education), 2023)
Inclusive learning compels all public schools to accommodate all learners and implement curricula that meet their needs. This study explored strategies for creating inclusive learning for learners who experience barriers to learning. Most of the literature on inclusive learning in schools has discussed the tension between theoretical approaches and the practical achievements of inclusive learning during teaching and learning. Furthermore, the local literature has demonstrated that educators try to modify and differentiate the existing curriculum with no tangible results for learners experiencing barriers to learning and not comprehending the content of the curriculum. This generic interpretive qualitative case study was conducted in the uMgungundlovu District (KwaZulu-Natal Province, South Africa), using semi-structured interviews with four teachers selected from four primary schools. Observations were conducted during teaching and learning, and documents were reviewed. The themes were derived and used through thematic data analysis to yield the study findings and draw conclusions. The study results indicated a shift toward inclusive learning, whereby learners experiencing barriers to learning can learn and better comprehend the curriculum's content through role-play, constructing objects, and drawing. Therefore, learners experiencing barriers to learning felt part of the teaching and learning process and could transform their contextual affordance into actions, which sheds light on their education journey.